SUGARCANE AGRIBUSINESS AND FOOD PRODUCTION IN THE MUNICIPALITY OF TUPI PAULISTA, STATE OF SAO PAULO, BRAZIL: CHALLENGES FOR THE FOOD SOVEREIGNTY - Valerio, Valmir Jose de Oliveira [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2016)
Different actors dispute specific forms of land use and management/control of territory, thus they contribute to the production of space in different ways, since their respective projects of society. These differences and territorial disputes are important to understand the diverse models of development of the countryside: promoted by peasant agriculture and promoted by agribusiness, and in this case, specifically the sugarcane agribusinesses. Given this, and using the concept of food sovereignty - the right of peoples to produce, in accordance with their own practices and cultural habits, through local food markets - as a referential concept and point of departure, this article postulates the following hypothesis to be verified: the territorialization of sugarcane agribusiness is resulting in more precarious conditions of production of food destined for local and regional consumption, deepening the dependence on the movement of food in the space, aggravating the establishment of food sovereignty. This article was developed from the case study of the municipality of Tupi Paulista, state of Sao Paulo, Brazil, on the period from 2003-2013.
Keywords: Sugarcane agribusiness; Food supply; Food sovereignty; Food dependency